Dissemination and Enrichment of Knowledge About Normal Birth to Bring About a Change to Society - Gouni, Olga; Hadjigeorgiou, Eleni; Ruiz-Berdún, Dolores; Minnie, Catharina Susanna; Calleja-Agius, Jean (My University, 2021)
The birth of a child is a pivotal time in the life of a mother, her family and society. The health and well-being of a mother and child at birth largely determines the future health and wellness of the entire family (World Health Organization (WHO), 2005). Normal birth has enormous benefits for mothers, neonates, families, and societies. The growing supportive evidence for the promotion of normal birth certainly relies on multidisciplinary collaborations to continue spreading knowledge about the advantages of normal birth and enhancing the understanding of how knowledge about normal birth can change society. Knowledge about normal birth varies among different groups of healthcare professionals, and it would be useful to identify how it is clinically translated to become accessible to other professionals and research teams, consumers, the public, significant decision- or policy makers, the industry, funding bodies, and volunteer health teams.
Keywords: Normal birth; Childbirth; Delivery; Knowledge transfer; Knowledge translation; Applied knowledge; Healthcare implementation; Research implementation; Childbirth research; Translational science